Did real economic uncertainty drive risk connectedness in the oil–stock nexus during the COVID-19 outbreak? A partial wavelet coherence analysis - Mohammad Al-Shboul; Aktham Maghyereh (Journal of Economic Structures, 2023)
Abstract This study explores the impact of real economic policy (business condition risk) on the oil–stock nexus risk connectedness during the COVID-19 pandemic. It uses multivariate wavelet coherency and partial wavelet coherency methods to isolate the effects of global risk indices, such as the US economic uncertainty index, the crude oil volatility index, and the geopolitical risk index, on risk connectedness. The study is based on daily data from January 2018 to December 2020 and finds a strong impact of real economic uncertainty indices on risk connectedness, with time-varying and frequency-sensitive patterns. The results also show that during the COVID-19 crisis, higher coherencies between oil and equity volatilities exist at lower frequencies. This research provides useful insights for regulators and portfolio diversifiers.